Analysis of the Impact of Blockchain Technology Adoption on Operational Efficiency and Consumer Trust in Digital Business - Nasir; Yuslinaini; Tarmizi (STMIK Indonesia Banda Aceh, 2024)
This research intends to assess the influence of blockchain technology adoption on operational efficiency and consumer trust in digital enterprises. Blockchain technology, with its decentralized, transparent and safe properties, is predicted to have a favorable impact on several elements of business operations and boost consumer trust. The research method employed is a quantitative approach by collecting data through surveys and interviews with organizations that have incorporated blockchain technology. Data analysis was carried out using descriptive and inferential statistical techniques to test the stated hypotheses. The research results demonstrate that the deployment of blockchain technology greatly boosts operational efficiency, particularly in terms of reduced transaction costs, increased processing speed, and reduced operational errors. Apart from that, customer confidence has also improved dramatically, notably in areas of openness, security and data protection. These findings demonstrate that blockchain technology not only contributes to enhancing the operational performance of enterprises, but also boosting the trust relationship between firms and consumers. The conclusion of this study is that the implementation of blockchain technology has a considerable positive influence on operational efficiency and consumer trust in digital enterprises. Therefore, organizations working in the digital ecosystem are recommended to explore integrating blockchain technology as a strategy to boost competitiveness and consumer trust.